Dystonia and the pedunculopontine nucleus: Current evidences and potential mechanisms - Su, Jun-hui; Hu, Yao-wen; Yang, Yi; Li, Ruo-yu; Teng, Fei; Li, Li-xi; Jin, Ling-jing (Frontiers in Neurology, 2022)
Being a major component of the midbrain locomotion region, the pedunculopontine nucleus (PPN) is known to have various connections with the basal ganglia, the cerebral cortex, thalamus, and motor regions of the brainstem and spinal cord. Functionally, the PPN is associated with muscle tone control and locomotion modulation, including motor initiation, rhythm and speed. In addition to its motor functions, the PPN also contribute to level of arousal, attention, memory and learning. Recent studies have revealed neuropathologic deficits in the PPN in both patients and animal models of dystonia, and deep brain stimulation of the PPN also showed alleviation of axial dystonia in patients of Parkinson's disease. These findings indicate that the PPN might play an important role in the development of dystonia. Moreover, with increasing preclinical evidences showed presence of dystonia-like behaviors, muscle tone changes, impaired cognitive functions and sleep following lesion or neuromodulation of the PPN, it is assumed that the pathological changes of the PPN might contribute to both motor and non-motor manifestations of dystonia. In this review, we aim to summarize the involvement of the PPN in dystonia based on the current preclinical and clinical evidences. Moreover, potential mechanisms for its contributions to the manifestation of dystonia is also discussed base on the dystonia-related basal ganglia-cerebello-thalamo-cortical circuit, providing fundamental insight into the targeting of the PPN for the treatment of dystonia in the future.